2023
DOI: 10.52547/ibj.3847
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Serum Levels of Tumor Necrosis Factor Alpha is associated with Histopathologic Progression of Gastric Cancer

Abstract: Background: The role of inflammatory cytokines, such as TNF-α and IL-8, in gastric carcinogenesis has been investigated, but their impact remains to be further elucidated. Methods: In this study, we measured the serum concentrations of these cytokines and H. pylori serostatus in dyspeptic patients, presenting with normal mucosa (NM = 53), chronic gastritis (CG = 94), and gastric cancer (GC = 82), by ELISA. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Research suggests that levels of CRP and IL-6 could be dependable markers for an inflammatory reaction linked to H. pylori infection [13,14]. This aligns with prior studies which propose that an infection from H. pylori can incite a long-term and continuous inflammation within the gastric mucosa [15].…”
Section: Discussionsupporting
confidence: 75%
“…Research suggests that levels of CRP and IL-6 could be dependable markers for an inflammatory reaction linked to H. pylori infection [13,14]. This aligns with prior studies which propose that an infection from H. pylori can incite a long-term and continuous inflammation within the gastric mucosa [15].…”
Section: Discussionsupporting
confidence: 75%
“…By adopting different proteomic approaches (e.g., ELISA and LC-MS) on cohorts of patients heterogeneous for both clinical characteristics (e.g., histology, stage) and sampling sizes, these works led to several putative biomarkers, thus confirming the high difficulty in discovering universal diagnostic markers, either as a single protein or as a panel of combined proteins, because of the highly complex biology of the disease. In particular, the ELISA-based technique targeted on analytes related to the immune system (sHLA-G [43,50], PD-1, and PD-L1 [45,61], inflammation (TNF-α [51,55], IL-6 [55,56,70]), ITIH4 [63,69,83], or digestion (PGI, PGII [53,55,81], and GKN1 [66]) is still the most used approach to investigate protein biomarkers in the blood of GC patients, as it has been over the last 10 years.…”
Section: Blood-based Circulating Biomarkersmentioning
confidence: 99%
“…A single protein failed to behave as an adequate diagnostic marker, which is consistent with the genetic heterogeneity of GC malignancy. Recently, very few targeted studies have focused on the characterization of only one blood protein as a putative diagnostic marker of GC (i.e., plasma sHLA-G [43,50], plasma DEK [48], and serum IGF-1), with most targeted works investigating more combined proteins (i.e., PD1 and PDL1 [45,61], PGI and PGII [53,55], cytokines, and, particularly, IL-6 [55,56,70] and TNF-α [51,55]. In this context, most recent studies have highlighted consistent improvements in specificity/sensitivity levels through the combination of more proteins into one panel test, gaining a level of diagnostic power that cannot be achieved by testing a single protein alone.…”
Section: Blood-based Circulating Biomarkersmentioning
confidence: 99%
“…It has been recently shown that there is a predominant T helper 17 response in Helicobacter pylori -infected patients with gastric adenocarcinoma and in Helicobacter pylori negative patients with autoimmune atrophic gastritis [ 33 , 34 , 35 , 36 , 37 ]. However, there are no clues on the pathogenic process mediated by Helicobacter pylori specific T helper 17 lymphocytes in human gastric intestinal metaplasia and gastric dysplasia.…”
Section: Introductionmentioning
confidence: 99%